kam3864
kam3864
02-02-2019
Mathematics
contestada
Solve the equation. 2x - 8(x+1)= 6(2x - 3)
Respuesta :
xotiffanyxoxo7169
xotiffanyxoxo7169
02-02-2019
ANSWER
[tex]x = \frac{5}{9} [/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 49+ )
Otras preguntas
Don't leave me all alone Just drop me off at home I'll be fine, it's not the first Just like last time but a little worse And she said that I'm not the one that
what is 4 1/2 plus 6 2/5
On Monday I Wilson Road 7 miles on the bike on Tuesday she wrote six miles on Wednesday she will Primo's father than she did Monday's and Tuesday's combined how
QUESTION 17 20. Which of the following is not a protein involved in muscle function? Catt troponin myosin tropomyosin actin QUESTION 18
Which phrase best completes the diagram?
In a symbiotic relationship, a. one organism benefits while its host gets nothing in return. b. bacteria takes food from your stomach, but does nothing for you.
Where the allies justified in using the atomic bombs to end the war ? why or why not ? PUT IN YOUR OWN WORDS.
Find the 9th term of the geometric sequence show below
Which equation is correct? O 3.3 = 32 = 9 4. 4 = 2(4) = 8 7.7 = 2(7) = 49 O 14 - 14 = 142 = 28
PLEASE HELP! Marius and his dad build a lamp in the shape of a triangular prism, open on the top and bottom 18 in. 20.1 in. 22 in. 18 in 18 in. How many square